2021
DOI: 10.1177/0145482x211028938
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Related Quality of Life and Its Sociodemographic Correlates Among Individuals With Visual Impairments

Abstract: Introduction: Visual impairment is an important public health concern worldwide that negatively affects quality of life (QOL). We aimed to assess the vision-related QOL and determine its sociodemographic correlates among individuals with visual impairments. Methods: We carried out a cross-sectional study during the years 2016–2017 among 201 individuals with visual impairments aged ≥ 40 years. After obtaining informed consent, we collected relevant information regarding sociodemographic characteristics using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Marques found that yoga was associated with self-perceived improvements in emotional, social, and physical health in patients with various medical conditions, including vision loss patients (Marquès-Brocksopp, 2014). Studies reported better quality of life in vision loss patients who practiced yoga compared to those who did not (Gagrani et al, 2018; Panigrahi et al, 2021). In addition, Jeter et al (2015) found that yoga interventions may negative psychosocial states, such as anxiety, depression, and stress, by providing postural stability and minimizing the fear of fallling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marques found that yoga was associated with self-perceived improvements in emotional, social, and physical health in patients with various medical conditions, including vision loss patients (Marquès-Brocksopp, 2014). Studies reported better quality of life in vision loss patients who practiced yoga compared to those who did not (Gagrani et al, 2018; Panigrahi et al, 2021). In addition, Jeter et al (2015) found that yoga interventions may negative psychosocial states, such as anxiety, depression, and stress, by providing postural stability and minimizing the fear of fallling.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that interventions involving meditation, breathing exercises, and yoga may play an important role in improving the physical health and functionality of children with vision loss. Studies on meditation and breathing exercises demonstrated self-perceived improvements in emotional, social, and physical health, a better quality of life, and improved negative psychosocial states, including depression, anxiety, and stress in adult vision loss patients (Gagrani et al, 2018;Jeter et al, 2015;Marquès-Brocksopp, 2014;Panigrahi et al, 2021). Falling is a significant concern for patients with vision loss; however, the improved postural stability from yoga and meditation exercises can help improve these negative psychological states (Roach et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Themes including financial hardship, lack of autonomy in healthcare access decision-making, prejudice and discrimination, and lack of disability-friendly health institutions and services are consistent with previous studies conducted in Nepal among women with disabilities [ 17 , 26 , 16 ]. The existing inequity in health care access due to disability has been established in general health services as well as in specific preventative health services including pap smear testing for cervical cancer as well as physical exercise, healthy diet, and safe sex programs [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, their daily activities, employment, and independence are negatively impacted [ 11 , 13 , 14 ]. Specifically, individuals with visual impairment have fewer opportunities for leisure activities and encounter financial challenges, including a higher likelihood of financial crises due to employment difficulties [ 15 , 16 ]. As visual impairment becomes more prevalent in an aging society, the declining quality of life for individuals with eye disorders is an increasingly significant concern.…”
Section: Introductionmentioning
confidence: 99%